A hierarchical model of mediation effect of motivation (MO) between internal marketing (IM) and service innovation (SI) - Soheila Raeisi; Meng Lingjie; Nur Suhaili Binti Ramli (Administrative Sciences, 2019)
This study investigates the mediation effect of motivation (MO) between internal marketing (IM) and service innovation (SI) using a hierarchical model. It adopts Bahman Group Corp of the automobile industry in Iran as a case study. This paper aims to examine the effect of internal marketing (IM) on service innovation (SI) by the mediation effect of motivation (MO). It develops a theoretical hierarchical multi-component model and analyses through a two-step approach of higher-order model by using PLS on 171 clean data. This research uses a survey method to collect data from the employees of Bahman Group Corp. The results indicate that motivation (MO) has a partial mediation effect between internal marketing (IM) and service innovation (SI). This study illustrates that internal communication (IC) and a New Organizational Delivery system (NOD) have the most substantial effect on internal marketing (IM) and service innovation (SI). Moreover, this research highlights to the service-based organisation to pay more attention to enhance internal marketing dimensions, especially in terms of service innovation to improve competitiveness. The results recommend further studies to examine the correlation between each indicator. The findings conclude with two main contributions and managerial implication to the research area that impactful to the subject of study.
Keywords: 350; internal marketing; service innovation; hierarchical multi-component model; smartPLS; the mediation effect